Tinjauan Kapasitas Dukung Teoritis Fondasi Kacapuri - Iskandar Iskandar (Universitas Lambung Mangkurat, 2000)
This article will discuss the Kacapuri Foundation and its bearing capacity. Kacapuri foundation is a specific kind of system, commonly and tradisionally used by the Banjarese, from generation to generation in wood structure building like house, school, etc, on soft soil area. The price of this foundation is low, becouse ot uses galam timber, witch is a very cheap. Galam is a plant, which grows in the swamp area in tropical forest.